Environmental risks in a laundry of the slaughtering and meat processing industry - da Silva, Vania Eugênia; Tavares Mafra, Simone Caldas; Mafra, Cláudio; de Souza, Amaury Paulo; Gomes, Elaine Cavalcante (Revista Gestão da Produção Operações e Sistemas, 2007)
Conditions in the work environment contribute to the occurrence of accidents and occupational illnesses, jeopardizingthe QLW (Quality of Life at Work) of the workers. In this sense, the objective was to identify thebiological, physical and ergonomic risks that a laundry in the slaughtering and meat processing industry offersto them. The biological risks are represented by microorganisms in their dirty clothes and in the air, and thenon-utilization of PPE’s (Personal Protective Equipment); the physical risks caused by the temperature, noiseand extreme humidity, as well as insufficient ventilation; the ergonomic risks caused by the adoption of incorrectpostures, imposed by deficiencies in the equipment and in the environment. These risks are aggravated bythe non-existence of standards for the organization in this type of laundry. It is suggested that the training forthe workers, installation of an extraction system, better ventilation and cross contamination barriers will leadto better work conditions.Keywords: Work accidents; Environmental risks; Laundry in the slaughtering and meat processing industry.